Hysteresis from monetary policy mistakes: how bad could it be? (2021)
What would happen if the central bank makes a mistake facing a crisis? This paper argues that it would leave scars in the long-run trend of production. If monetary policy is not expansionary-enough during crises, an inefficient rise of the interest rate intensifies the scarring effects of recessions. The hysteresis effect comes from higher innovation costs that induce a drop in productivity growth, an indiscriminate firms' exit process, and a rise in unemployment. This article presents a theoretical model that rationalizes these mechanisms. The theory suggests that, in the long-run, even though growth recovers to its pre-shock rate and the economy converges to full firms' survival and full employment, the long-term output level is persistently lower than the level it would have reached in the absence of errors. How costly are monetary policy mistakes?